ML based career suggestive system for informal job sector considering cognitive skills - Tonny, Ms. Ayesha Siddika; Hafsa; Lavlu, Md. Tousif Hasan; Ghosh, Abhijit Kumar; Roy, Sourojit (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.